1998
DOI: 10.1016/s0896-6273(00)80477-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Discrimination of Temporal Patterns by Motion-Sensitive Neurons in Primate Visual Cortex

Abstract: Although motion-sensitive neurons in macaque middle temporal (MT) area are conventionally characterized using stimuli whose velocity remains constant for 1-3 s, many ecologically relevant stimuli change on a shorter time scale (30-300 ms). We compared neuronal responses to conventional (constant-velocity) and time-varying stimuli in alert primates. The responses to both stimulus ensembles were well described as rate-modulated Poisson processes but with very high precision (approximately 3 ms) modulation functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
336
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(381 citation statements)
references
References 33 publications
39
336
2
Order By: Relevance
“…Our results are consistent with those obtained in Buracas et al (1998) which show a difference between the direct and indirect methods of estimating information rates. Our results further imply that information from bursting neurons can only be efficiently decoded by non-linear means while linear decoding will be effective for tonic neurons.…”
Section: Information Theory: Linear Versus Nonlinear Codingsupporting
confidence: 92%
“…Our results are consistent with those obtained in Buracas et al (1998) which show a difference between the direct and indirect methods of estimating information rates. Our results further imply that information from bursting neurons can only be efficiently decoded by non-linear means while linear decoding will be effective for tonic neurons.…”
Section: Information Theory: Linear Versus Nonlinear Codingsupporting
confidence: 92%
“…Overall, the degree of precision of spiking in response to repeated presentations of the same stimulus appears to decrease along the visual pathway 50 , whereas spike-count variability increases 42,43,47,[51][52][53] . This could be due to the presence of background cortical activity, in which case a method to uncover the stimulus-locked precision is needed (FIG.…”
Section: Evidence For Spike-time Precision In the Visual Systemmentioning
confidence: 97%
“…Neurons in the mediotemporal cortex in turn receive inputs from the primary visual cortex and respond to motion. It has been shown that neurons in the mediotemporal cortex respond precisely to rapid changes in the direction of motion 47 . The reliability of events in these spike trains was initially found to be low; however, a re-analysis revealed multiple reliable spike-time patterns 18 .…”
Section: Evidence For Spike-time Precision In the Visual Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sensory cortex encodes stimuli that fluctuate over few tens of milliseconds 6,7 , whereas in association cortex behavioral choices can require the maintenance of information over seconds 8,9 . However, it remains poorly understood if diverse timescales result mostly from features intrinsic to individual neurons or from neuronal population activity.…”
mentioning
confidence: 99%